Protection against acute adriamycin-induced cardiotoxicity by garlic: Role of endogenous antioxidants and inhibition of TNF-α expression - Mukherjee, Sumanta; Banerjee, Sanjay Kumar; Maulik, Mohua; Dinda, Amit Kumar; Talwar, Kewal K; Maulik, Subir Kumar (BMC pharmacology, 2003)
Oxidative stress is the major etiopathological factor in adriamycin-induced cardiotoxicity. Relatively low amounts of endogenous antioxidant makes the heart vulnerable to oxidative stress-induced damage. Chronic oral administration of garlic has been reported to enhance the endogenous antioxidants of heart. We hypothesized that garlic-induced enhanced cardiac antioxidants may offer protection against acute adriamycin-induced cardiotoxicity. Rats were either administered freshly prepared garlic homogenate (250 and 500 mg/kg daily, orally, for 30 days) or probucol (cumulative dose, 120 mg/kg body weight divided in 12, i.p. over a period of 30 days) or double distilled water (vehicle), followed by a single dose of adriamycin (30 mg/kg i.p.). In the adriamycin group, increased oxidative stress was evidenced by a significant increase in myocardial TBARS (thiobarbituric acid reactive substances) and decrease in myocardial SOD (superoxide dismutase), catalase and GPx (glutathione peroxidase) activity. Histopathological studies showed focal as well as subendocardial myocytolysis with infiltration of macrophages, lymphocytes and edema. Immunocytochemistry showed marked expression of TNF-alpha (tumor necrosis factor-alpha) in the myocardium. Increase in myocardial TBARS and decrease in endogenous antioxidants by adriamycin was prevented significantly in the garlic treated rat hearts, which was comparable to the probucol-treated group. Histopathological evidence of protection was also evident in both garlic-treated and probucol-treated groups. Probucol, 250 mg/kg and 500 mg/kg of garlic reduced adriamycin induced TNF-alpha expression in the myocardium and was associated with reduced myocyte injury. It is concluded that chronic garlic administration prevents acute adriamycin-induced cardiotoxicity and decreases myocardial TNF-alpha expression.